The regional challenges in the post-Covid era - Annalisa Caloffi; Marusca De Castris; Giovanni Perucca (FrancoAngeli, 2022)
The XLII AISRe Conference, held online between 8 and 10 September 2021, called the Italian community of regional and urban scientists to debate on the long-term consequences, issues and challenges imposed by the coronavirus global emergency. These challenges concern the asymmetric consequences of the public health emergency across places and within societies. In fact, in a world already characterized by increasing social inequalities, the pandemic is likely to exacerbate the rise of disparities. Limited mobility, the restricted access to public services such as schools and hospitals, and the higher uncertainty generated by the healthcare emergency hit more severely those individuals in a condition of relative economic, occupational, and educational disadvantage. The territorial implications of these phenomena are extremely relevant, and still understudied. They mainly concern two dimensions: the first one refers to the differentiated impact of the pandemic on the inequalities across places; the second one concerns the differentiated impact of the pandemic on the inequalities within places. The effect of the Covid pandemic on inequalities cumulates with the one of other deep socioeconomic transformations, as those induced in the production sector and job market by the rise of the Industry 4.0 paradigm. In such framework, the role of public policies becomes fundamental, in order to mitigate the undesired effects of these phenomena and to amplify the positive ones. The present book collects a selection of the many interesting studies, presented during the XLII AISRe Conference, that were devoted to the abovementioned issues. More in details, the book is structured into three parts. The first section supplies fresh evidence on the levels and trends of socioeconomic disparities across and within regions. The second section investigates the determinants of these trends, pointing in particular to the role of the unprecedented transformations occurring in the economic structure and job markets of regions and cities. Finally, the third section of the book focuses on the policy tools to face the challenges emerged in the previous discussion.
Keywords: 330